ANALISIS PELAN INDUK PEMBANGUNAN PENDIDIKAN (PIPP) 2006-2010 DIGUBAL BERDASARKAN PEMBANGUNAN PENDIDIKAN MALAYSIA (2001-2010) - Hj Marzuki, Shahril @ Charil; Hayati Ahmad, Norfizah; A. Gani, Muhammad Faizal (Jurnal Internasional Manajemen Pendidikan, 2012)
This article examines and analyzes critically the National Education Blueprint (NEB) (PIPP) (2006- 2010) which has six main trusts: (i) building the nation and people that is united and pround of its national identity, (ii) developing human capital that is knowledgeable and skilled with an appreciation of pure values, (iii) strengthening national schools, making national schools the main choice without obstructing the development of vernacular schools, (iv) narrowing the education gap in term of location, socio-economic status and students abilities so that all schools and students will be given the same opportunities to achieve exellence, (v) improving teaching profession, and (vi) accelerating excellence at educational institution, through cluster schools (which are centres of excellence) so that they will become showcase or model schools.Whether the NEB had been formulated based on Vision 2020, which have nine main strategies, the Education Development Plan ( 2001- 2010 ) which has four main thrusts, namely (i) increase acess in education, (ii) increase equity in education, (iii) improve quality in education, and (iv) improve efficiency and effectiveness of education management and whilst the Ninth Malaysia Plan which has six core strategies namely (i) improveing the access to and quality of the education system at all levels, (ii) making national schools the school of choice, (iii) Producing tertiary institution of international standing, (iv) nurturing top quality research and development and scientific and innovation, and (v) Empowering women and youth and (vi) fostering a society with strong values. It is also discussed the issues and implementation of NEB.